Blur‐Free Outcoupling Enhancement in Transparent Organic Light Emitting Diodes: A Nanostructure Extracting Surface Plasmon Modes. Issue 10 (11th July 2013) - Choi, Chung Sock; Kim, Dong‐Young; Lee, Sung‐Min; Lim, Myung Sub; Choi, Kyung Cheol; Cho, Hyunsu; Koh, Tae‐Wook; Yoo, Seunghyup
<x xml:space="preserve">Abstract</x> A nanostructured transparent organic light emitting diode (TrOLED) with a periodically perforated tungsten trioxide (WO3) layer is proposed to improve the light extraction efficiency of TrOLEDs. The embedded nanostructure enhances the outcoupling of the waveguide modes and the surface plasmon mode. Improved outcoupling efficiency can be achieved with negligible influence on the transmittance or optical clarity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>